THE IMPACT OF AGE, SEX, AND SOCIO-ECONOMIC STATUS ON SERUM VITAMIN B12, FOLATE CONCENTRATION AND IRON STATUS IN TURKISH CHILDREN: A CROSS-SECTIONAL STUDY - Hacer Eroğlu İçli; Arif Murat Kaytaz; Emre Akkaya; Evin Ademoğlu; Sema Genç (İstanbul Tıp Fakültesi Dergisi)
Objective: The aim of this study is to evaluate the effects of age, sex, and socio-economic status (SES) on concentrations of vitamin B12 (vit-B12), folate, iron, and ferritin through the pediatric age span, and to show the relationship of these nutrients with blood count parameters such as hemoglobin (Hb), hematocrit (Hct), mean corpuscular volume (MCV), and red cell distribution (RDW). Material and Method: The study comprised of 30,504 venous blood samples (54.5% of girls and 45.5% of boys). The study group was stratified; group I: 1-6 years (n=3,870), group II: 7-12 years (n=11,019), and group III: 13-18 years (n=15,615). Serum vit-B12, folate, ferritin, iron and total iron-binding capacity (TIBC) were measured using a Beckman Coulter DXI 800, and the blood count was analyzed using a Sysmex XE 2100 analyzer. Results: The Hb, Hct, MCV, and RDW levels were significantly different between the age groups of boys and girls (p<0.001, for all). Hb and Hct were the highest in boys aged 13-18 years, and higher than those of girls in the same age group (p<0.001). The MCV and RDW were also significantly different across the age groups (p<0.001). The iron deficiency prevalences were 12.3% and 4.2% for the girls and boys respectively. Serum folate and vit-B12 showed decrement with age across the age groups. The prevalences of vit-B12 deficiency were 27.1% and 28.3% and 6.0% and 6.8% for folate deficiency for girls and boys. Iron, TIBC,and ferritin levels were significantly different between the high and medium SES. Conclusion: The results of this study are important in that the monitorization of ferritin, vit-B12, and folate levels greatly contribute to clinical practice because of the roles of vit-B12, folate, and iron in mental, emotional, and metabolic development. However, there is a need for larger and multicenter studies that can represent the nutrients of Turkish children and adolescents nationwide.